As others see us - Prentis, Nicolas (United Kingdom Cambridge University Press, 2014)
Soon after Gemma gets a new phone, strange things start happening. Despite not studying, she's suddenly getting top marks in every subject. Her tennis skills improve dramatically, attracting the attention of the best-looking boy in the school. And everyone wants to be her friend. But how has this happened ? And is this new Gemma, the real Gemma ?
Cambridge Experience Readers, previously known as Cambridge Discovery Readers, is an exciting series of original fiction, adapted fiction and factbooks, specifically written for pre-teen and teenage learners of English.
Contents.
Keywords: Reading books; English language; Fantasy; Elementary/lower-intermediate level